Hospital outbreak of linezolid-resistant and vancomycin-resistant ST80 Enterococcus faecium harbouring an optrA-encoding conjugative plasmid investigated by whole-genome sequencing. Issue 4 (August 2020) - Egan, S.A.; Corcoran, S.; McDermott, H.; Fitzpatrick, M.; Hoyne, A.; McCormack, O.; Cullen, A.; Brennan, G.I.; O'Connell, B.; Coleman, D.C.
Summary: Background: Linezolid is an antibiotic used to treat infections caused by multi-drug-resistant Gram-positive bacteria. Linezolid resistance in enterococci has been reported with increasing frequency, with a recent rise in resistance encoded by optrA, poxtA or cfr. Aim: To investigate a hospital outbreak of linezolid- and vancomycin-resistant Enterococcus faecium (LVREfm) using whole-genome sequencing (WGS). Methods: Thirty-nine VREfm from patient screening (19 isolates, 17 patients) and environmental sites (20 isolates) recovered in October 2019 were investigated. Isolates were screened using polymerase chain reaction for optrA, poxtA and cfr, and underwent Illumina MiSeq WGS. Isolate relatedness was assessed using E. faecium core genome multi-locus sequence typing (cgMLST). One LVREfm underwent MinION long-read WGS (Oxford Nanopore Technologies) and hybrid assembly with MiSeq short-read sequences to resolve an optrA -encoding plasmid. Findings: Twenty isolates (51.3%) were LVREfm and optrA- positive, including the LVREfm from the index patient. A closely related cluster of 28 sequence type (ST) 80 isolates was identified by cgMLST, including all 20 LVREfm and eight linezolid-susceptible VREfm, with an average allelic difference of two (range 0–10), indicating an outbreak. Nineteen (95%) LVREfm harboured a 56, 684-bp conjugative plasmid (pEfmO_03). The remaining LVREfm exhibited 44.1% sequence coverage to pEfmO_03. The presence of pEfmO_03 in LVREfm and the close relatedness of the outbreak cluster isolates indicated the spread of a single strain. The outbreak was terminated by enhanced infection prevention and control (IPC) and environmental cleaning measures, ceasing ward admissions and ward-dedicated staff. Conclusion: WGS was central in investigating an outbreak of ST80 LVREfm. The rapid implementation of enhanced IPC measures terminated the outbreak.